Time‐Dependent Afterglow Color in a Single‐Component Organic Molecular Crystal - Wang, Jian‐Xin; Fang, Ye‐Guang; Li, Chun‐Xiang; Niu, Li‐Ya; Fang, Wei‐Hai; Cui, Ganglong; Yang, Qing‐Zheng (Angewandte Chemie International Edition, 2020)
An organic crystal of 4,4′‐bis(N‐carbazolyl)‐1,1′‐biphenyl (pCBP) exhibits time‐dependent afterglow color from blue to orange over 1 s. Both experimental and computational data confirm that the color evolution results from well‐separated, long‐persistent thermally activated delayed fluorescence (TADF) and room‐temperature phosphorescence (RTP) with different but comparable decay rates. TADF is enabled by a small S1–T1 energy gap of 0.7 kcal mol−1. The good separation of TADF and RTP is due to a 11.8 kcal mol−1 difference in the S0 energies of the S1 and T1 structures, indicating that apart from the excited‐state properties, tuning the ground state is also important for luminescence properties. This afterglow color evolution of pCBP allows its applications in anticounterfeiting and data encryption with high security levels. Organic sunset: A time‐dependent afterglow color in a single‐component organic molecular crystal was observed. It originates from well‐separated, long‐persistent thermally activated delayed fluorescence and room‐temperature phosphorescence with different but comparable decay rates.